1990
DOI: 10.1021/bi00486a027
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin activation on membranes with anionic lipids containing phosphate, sulfate and/or carboxyl groups

Abstract: Factor Xa catalyzed prothrombin activation is strongly stimulated by the presence of negatively charged membranes plus calcium ions. Here we report experiments in which we determined the prothrombin-converting activity of phosphatidylcholine (PC) membranes that contain varying amounts of different anionic lipids, viz., phosphatidylserine (PS), phosphatidic acid (PA), phosphatidylmethanol (MePA), phosphatidylglycerol (PG), phosphatidylethanolamine (PE), phosphatidyl-beta-lactate (PLac), sulfatides (SF), sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 24 publications
(37 reference statements)
3
32
1
Order By: Relevance
“…Thus, one possible explanation for our results is that increased PTase activity is due to increased membrane disorder, at least to a point. This would be consistent with reports that oleate chains accelerate PTase activity (10,11), and it is compatible with the suggestion that PTase activity is sensitive to the precise way in which its components are juxtaposed on a membrane (6). Even if this is not the sole explanation for accelerated PTase, the relatively short acyl chains of DMPC/ DMPS may amplify the effects of the direct cause.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, one possible explanation for our results is that increased PTase activity is due to increased membrane disorder, at least to a point. This would be consistent with reports that oleate chains accelerate PTase activity (10,11), and it is compatible with the suggestion that PTase activity is sensitive to the precise way in which its components are juxtaposed on a membrane (6). Even if this is not the sole explanation for accelerated PTase, the relatively short acyl chains of DMPC/ DMPS may amplify the effects of the direct cause.…”
Section: Resultssupporting
confidence: 92%
“…This difference was evident even after accounting for changes in substrate transport due to altered lipid "fluidity" and was confirmed using the soluble substrate, prethrombin-1. Other investigators (6,11) have also used prethrombin-1 and found no such effect, but they nonetheless observed that PTase activity is accelerated by phosphatidylcholine vesicles if unsaturated acyl chains were present, especially at relatively low concentrations of phosphatidylserine.…”
mentioning
confidence: 98%
“…27 The rate of prothrombin activation is dependent on the assembly of tenase and prothrombinase complexes, which in turn depends on the presence of surfaces enriched in negativelycharged phospholipids. 28 The increased number of microparticles of platelet origin observed in association with large aneurysms is likely to provide the phosphatidylserine-enriched membranes required to favor thrombin generation. 29 Microparticles are the main link between platelet activation and thrombin generation.…”
Section: Touat Et Almentioning
confidence: 99%
“…Optimum prothrombinase activity has been reported for membranes that contain at least 10 mol % phosphatidylserine (11)(12)(13)(14). It is rationalized that this dependence is the result of the lower binding affinity of membranes with low phosphatidylserine content for the protein constituents of the enzyme complex (factor Xa and factor Va) as well as for its substrate prothrombin (15)(16)(17).…”
mentioning
confidence: 99%